Conservative Difference Scheme for Generalized Rosenau-KdV Equation. (14th May 2014) - Luo, Yan; Xu, Youcai; Feng, Minfu
Abstract : A conservative Crank-Nicolson finite difference scheme for the initial-boundary value problem of generalized Rosenau-KdV equation is proposed. The difference scheme shows a discrete analogue of the main conservation law associated to the equation. On the other hand the scheme is implicit and stable with second order convergence. Numerical experiments verify the theoretical results.